Phenomenological case study of spiritual connectedness in the academic workplace - Wan Nasir, Zaireena (Human Resource Management Academic Research Society, 2019)
The field of workplace spirituality is plagued by problems of definition due to the ambiguity of the term “spirituality” from the Western perspective. As workplace spirituality is by nature an ephemeral phenomenon approachable from multiple perspectives, this study approaches this topic from the Islamic perspective. The inductive research method chosen is a combination of phenomenology and qualitative case study. Phenomenology is chosen as it describes the meaning for individuals of their lived experiences of a phenomenon. The International Islamic University of Malaysia is chosen as the case study due to its prominence as a premier global Islamic university. In-depth interviews with academics, both local and international, of the International Islamic University of Malaysia are the primary method of data collection. Thirteen academics, six males and seven females, from this university have been interviewed for this purpose. Findings suggest that spiritual connectedness is about the relationship with Allah and the relationship with human beings (habluminallah wa habluminannas), God consciousness (taqwa), sense of belonging, doing for the sake of Allah, brotherhood (ukhuwwah), inviting towards what is good and forbidding from wrong (amar ma’ruf nahi mungkar) and ihsan. The implication of these findings highlights the understanding of Muslim academics of what being spiritually connected mean to them personally. The contribution of this study is to enrich the literature on workplace spirituality by exploring the Islamic perspective of spiritual connectedness and to understand first-hand how being spiritually connected is defined by Muslim academics.